Warming lignocaine reduces the pain of injection during peribulbar local anaesthesia for cataract surgery. - Bell, R W (1995)
AIMS--To test if the simple technique of warming lignocaine reduces the pain of injection during local anaesthetic cataract surgery. METHODS--Sixty patients undergoing peribulbar local anaesthesia for cataract surgery were allocated randomly to receive either warm (37 degrees C) or cold (room temperature) plain 2% lignocaine for the injection. Pain was assessed subjectively by asking the patients to score their pain from 0 (no pain) to 10 (most severe pain imaginable). RESULTS--The mean pain score for the warm group was 2.3 (SD 1.3) in comparison with a mean score of 5.5 (1.0) for the cold group (p < 0.01). CONCLUSIONS--The process of warming lignocaine to 37 degrees C has been found to reduce significantly the pain of injection during peribulbar local anaesthesia. It is recommended that this technique be more widely adopted in order to minimise patient's discomfort.